Effectiveness of a homeopathic complex medicine in infantile colic: A randomized multicenter study. (August 2019) - Raak, Christa; Krueger, Peter; Klement, Petra; De Jaegere, Sabine; Weber, Stephan; Keller, Thomas; Ilyenko, Lydia; Martin, David; Ostermann, Thomas
Highlights: What is known Infantile colic has a prevalence of around 20%, impacting child and parental quality of life. Despite some evidence on the use complementary therapies in infantile colic, literature on homeopathic medications is scarce. What is new Enterokind was significantly more effective than Simethicone in reducing infantile colic complaints and symptoms after 10 days of treatment. Enterokind was shown to be a safe and well tolerated treatment. Abstract: Objectives: Infantile colic is a common benign disease occurring in early infancy that may have a great impact on family life. In the present study, the effectiveness and safety of the complex homeopathic medicine Enterokind was compared with Simethicone for treating infantile colic. Design and setting: Current data were drawn from a prospective, multicenter, randomized, open-label, controlled clinical trial that was conducted in 2009 in 3 Russian outpatient clinics. Children received either Enterokind ( Chamomilla D6, Cina D6, Colocynthis D6, Lac defloratum D6 and Magnesium chloratum D6) or Simethicone. Data from infants ≤ 6 months with infantile colic are presented here. Main outcome measures: The main outcomes assessments were the change of total complaints score (maximum 17 points) and total objective symptoms score (maximum 22 points) after 10 days of treatment. Results: Data from 125 infants ≤ 6 months with infantile colic were analyzed. The differences in total complaints and objective symptoms scores between baseline and day 10, estimated from the ANCOVA model, were found to be highly significant (p < 0.0001; ITT) in favor of Enterokind, both for complaints (Δ=-2.38; 95% confidence interval (CI): [-2.87; -1.89]) and for objective symptoms (Δ=-2.07; 95% CI: [-2.65; -1.49]). 1 adverse event (AE), vomiting, occurred under Enterokind and was rated to be unlikely related to it; 4 AEs occurred under Simethicone. All AEs were non-serious. Conclusions: The current study indicates that Enterokind is an effective and safe homeopathic treatment for functional intestinal colic in infants ≤ 6 months.